ĐK:...(1)⇔(1−y)(√x−y−1)+(x−y−1)=(x−y−1)√y⇔(x−y−1)(1−y√x−y+1+1−√y)=0⇔(x−y−1)(1−y)(1√x−y+1+1√y+1)=0⇔x=y+1ory=1(do(...)>0)*)y=1:(2)tt:9−3x=0⇔x=3*)x=y+1(2)tt:2y2+3y−2=√1−y⇔2(y2+y−1)=√1−y−y⇔(y2+y−1)(1√1−y+y+2)=0⇔y2+y−1=0⇔y=−1+√52(t/m đk)⇒x=1+√52KL:....
ĐK:...(1)⇔(1−y)(√x−y−1)+(x−y−1)=(x−y−1)√y⇔(x−y−1)(1−y√x−y+1+1−√y)=0⇔(x−y−1)(1−y)(1√x−y+1+1√y+1)=0⇔x=y+1ory=1(do(...)>0)*)y=1:(2)tt:9−3x=0⇔x=3*)x=y+1(2)tt:2y2+3y−2=√1−y⇔2(y2+y−1)=√1−y−y⇔(y2+y−1)(1√1−y+y+2)=0⇔y2+y−1=0⇔y=−1+√52(t/m đk)⇒x=1+√52
ĐK:...
(1)⇔(1−y)(√x−y−1)+(x−y−1)=(x−y−1)√y⇔(x−y−1)(1−y√x−y+1+1−√y)=0⇔(x−y−1)(1−y)(1√x−y+1+1√y+1)=0⇔x=y+1ory=1(do(...)>0)*)
y=1:(2)tt:
9−3x=0⇔x=3*)
x=y+1(2)tt:
2y2+3y−2=√1−y⇔2(y2+y−1)=√1−y−y⇔(y2+y−1)(1√1−y+y+2)=0⇔y2+y−1=0⇔y=−1+√52(t/m đk)
⇒x=1+√52KL:....